2021
DOI: 10.1016/j.jadohealth.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing COVID-19 Content Posted to TikTok: Public Sentiment and Response During the First Phase of the COVID-19 Pandemic

Abstract: Purpose The purpose of this study was to characterize COVID-19 content posted by users and disseminated via TikTok, a social media platform that has become known largely as an entertainment platform for viral video-sharing. We sought to capture how TikTok videos posted during the initial months of the COVID pandemic changed over time as cases accelerated. Methods This study is an observational analysis of sequential TikTok videos with #coronavirus from January to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 25 publications
1
59
0
3
Order By: Relevance
“…In general, the general public's concept of risk is likely to be poor, and this contributes to a sense of uncertainty and confusion. Therefore, during COVID-19 health information communication, it is important to emphasize the importance of: ( 1 ) honesty during times of uncertainty, ( 2 ) being transparent with the public about what is and is not known and the rapid development of new knowledge, ( 3 ) the use of clear and consistent language, ( 4 ) where possible, by consistent spokespeople who can demonstrate honesty, and ( 5 ) confidence in making decisions while demonstrating empathy and concern ( 84 , 85 ). Second, during COVID-19 pandemic, the key messages about wearing masks, washing hands, maintaining social distances, and vaccination are essential to help combat the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, the general public's concept of risk is likely to be poor, and this contributes to a sense of uncertainty and confusion. Therefore, during COVID-19 health information communication, it is important to emphasize the importance of: ( 1 ) honesty during times of uncertainty, ( 2 ) being transparent with the public about what is and is not known and the rapid development of new knowledge, ( 3 ) the use of clear and consistent language, ( 4 ) where possible, by consistent spokespeople who can demonstrate honesty, and ( 5 ) confidence in making decisions while demonstrating empathy and concern ( 84 , 85 ). Second, during COVID-19 pandemic, the key messages about wearing masks, washing hands, maintaining social distances, and vaccination are essential to help combat the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it was suggested that the increasing use of social networking media can supplement eHealth literacy (16). During the COVID-19 pandemic, it is apparent that social networking platforms such as Twitter, YouTube, TikTok, Facebook, and others played significant roles in providing and exchanging health information (3)(4)(5)(6). In a recently proposed wedding cake model of health information (6), social media is depicted as the largest and last segment of the wedding cake, and it represents the vast amount of nearly unfiltered and uncontrolled information generated or amplified by the public.…”
Section: Improving Ehealth Literacy: Significance and Challengesmentioning
confidence: 99%
See 3 more Smart Citations